Effectiveness of nanoatrazine in post-emergent control of the tolerant weed Digitaria insularis - Sousa, Bruno Teixeira; Santo Pereira, Anderson do Espírito [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; de Oliveira, Halley Caixeta; Dalazen, Giliardi (Polish Academy of Sciences Chancellery, 2020)
Digitaria insularis (sourgrass) is a monocotyledon weed of difficult control and high invasive behavior. Atrazine is widely applied in the Americas to control weeds in maize culture, but its efficiency against D. insularis is limited. The incorporation of atrazine into poly(epsilon-caprolactone) nanocapsules increased the herbicidal activity against susceptible weeds; however, the potential of this nanoformulation to control atrazine-tolerant weeds including D. insularis has not yet been tested. Here, we evaluated the post-emergent herbicidal activity of nanoatrazine against D. insularis plants during initial developmental stages. The study was carried out in a greenhouse, using pots filled with clay soil. Plants with two or four expanded leaves were treated with conventional or nanoencapsulated atrazine at 50 or 100% of the recommended dosage (1,000 or 2,000 g ∙ ha−1), followed by the evaluation of physiological, growth, and control parameters of the plants. Compared with conventional herbicide, both dosages of nanoatrazine induced greater and faster inhibition of D. insularis photosystem II activity at both developmental stages. Atrazine nanoencapsulation also improved the control of D. insularis plants, especially in the stage with two expanded leaves. In addition, nanoatrazine led to higher decreases of dry weight of four-leaved plants than atrazine. The use of the half-dosage of nanoatrazine was equally or more efficient in affecting most of the evaluated parameters than the conventional formulation at full dosage. Overall, these results suggest that the nanoencapsulation of atrazine potentiated its post-emergent herbicidal activity against D. insularis plants at initial developmental stages, favoring the control of this atrazine-tolerant weed.
Keywords: Atrazine; Chemical control; Nanoherbicide; Nanotechnology; Sourgrass; Tolerant weed control